First record of the seed beetle Bruchidius siliquastri (Coleoptera, Chrysomelidae, Bruchinae) from Greece - Georgios Gastouniotis; Athanasios Boulas; Panagiotis Gastouniotis (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2024)
Bruchidius siliquastri Delobel, 2007, a chrysomelid species presumably of East Asian origin, is recorded for the first time in Greece. It is regarded as an invasive species in Europe that feeds on the seeds of Cercis siliquastrum L. (Fabaceae). The species distribution and ecology are briefly discussed. An additional record of Bruchidius terrenus (Sharp 1886) in Greece is also provided.